Review Article about Heart Rate Monitoring System - Jassim, Ahmed Riyadh Latif; Ali, Zuher Ehab Adnan; Ajlan, Hussein Hayder Oudah; Hozaim, Mohammed Talib Sabhan (American Journal of Botany and Bioengineering, 2025)
Heart rate monitoring is essential for assessing cardiovascular health, fitness levels, and early detection of irregularities. Despite advancements in wearable technologies, there remain challenges in accuracy, affordability, and real-time monitoring. This study presents the design and implementation of an Arduino-based heart rate monitoring system using a fingertip sensor and pulse oximetry principles. The system captures blood flow variations through an infrared sensor, processes the data via a microcontroller, and displays real-time results on an LCD screen. Findings indicate that the device provides reliable heart rate measurements comparable to standard medical devices, offering a cost-effective and portable solution for continuous heart rate tracking. These results emphasize the potential of integrating such systems with IoT and mobile applications for enhanced remote healthcare monitoring.